2016
DOI: 10.13040/ijpsr.0975-8232.7(2).607-17
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT:In the present study, Marumoside A isolated from Moringa oleifera, a traditional medicinal plant, was synthesized for the first time using trichloroacetimidate donor as a key step. The aglycone 4-hydroxy phenylacetamide was prepared from 4-hydroxyphenyl acetic acid using oxallyl chloride and aqueous ammonia. The lipid derivatives of Marumoside A were synthesized using different fatty amines. The anti-inflammatory activity of the Marumoside A and its lipid derivatives was evaluated for the inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Epidemiological studies have consistently shown that high intake of flavonoids has protective effects against many infectious diseases and against cardiovascular, kidney and neurodegenerative diseases, cancers, and other age-related diseases (Kou et al, 2018;Leone et al, 2015;Siddhuraju & Becker, 2003). The presence of alkaloids, a family of cyclic organic secondary metabolic compounds containing nitrogen, has also been confirmed in The Plant Genome moringa leaves, notably marumoside A and marumoside B together with pyrrolemarumine-4″-O-α-L-rhamnopyranoside (Sahakitpichan et al, 2011), for which cardioprotective, anti-inflammatory and antihypertensive effects have been described (Dangi et al, 2002;Panda et al, 2013;Vudhgiri et al, 2016). Finally, glucosinolates, a family of sulfurcontaining secondary metabolites synthesized from amino acids in Brassicaceae species and related families from the Brassicales order, are also produced in all parts of the moringa plant, particularly in the form of aromatic glucosinolates derived from tryptophan and others from phenylalanine (Bennett et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have consistently shown that high intake of flavonoids has protective effects against many infectious diseases and against cardiovascular, kidney and neurodegenerative diseases, cancers, and other age-related diseases (Kou et al, 2018;Leone et al, 2015;Siddhuraju & Becker, 2003). The presence of alkaloids, a family of cyclic organic secondary metabolic compounds containing nitrogen, has also been confirmed in The Plant Genome moringa leaves, notably marumoside A and marumoside B together with pyrrolemarumine-4″-O-α-L-rhamnopyranoside (Sahakitpichan et al, 2011), for which cardioprotective, anti-inflammatory and antihypertensive effects have been described (Dangi et al, 2002;Panda et al, 2013;Vudhgiri et al, 2016). Finally, glucosinolates, a family of sulfurcontaining secondary metabolites synthesized from amino acids in Brassicaceae species and related families from the Brassicales order, are also produced in all parts of the moringa plant, particularly in the form of aromatic glucosinolates derived from tryptophan and others from phenylalanine (Bennett et al, 2003).…”
Section: Introductionmentioning
confidence: 99%